Effect of Paternal Body Mass Index on Cumulative Live Birth Rates: Retrospective Analysis of 3048 Embryo Transfers in Couples Using Autologous Gametes - Laura Mossetti; Irene Hervás-Herrero; María Gil-Juliá; Ana Navarro Gomez-Lechon; Rosa María Pacheco-Rendón; Rocío Rivera-Egea; Nicolás Garrido-Puchalt (Cells)
Obesity is a multifactorial disease present worldwide and correlated with hormonal alterations that may cause a decrease in reproductive outcomes and seminal quality. However, the specific mechanisms involved are unknown. This led us to examine the relationship between paternal body mass index (BMI) and clinical reproductive outcomes by evaluating the cumulative live birth rates (CLBRs) per number of embryo transfers (ETs), embryos replaced (EmbRs), and oocytes used (OUs) in consecutive treatments until achieving the first newborn. A retrospective study was performed, and Kaplan–Meier survival curves were created to observe CLBRs with regard to the paternal BMI, adjusted by relevant confounders through Cox regression models. The participants were couples undergoing intracytoplasmic sperm injection (ICSI) and ET in Spanish IVIRMA clinics using autologous gametes. The cohort was subdivided based on paternal BMI: normal (18.5–24.99 kg/m2) (N), overweight (25–29.99 kg/m2) (OV), or obese (≥30 kg/m2) (OB) patients. A total of 4750 ICSI cycles were included, encompassing 49,485 mature oocytes, 23,963 blastocysts, and 3048 ETs. When calculating CLBRs based on the number of ETs carried out until live birth was achieved, no statistically significant differences were found (p = 0.72). After adjusting for maternal age and BMI, female infertility diagnosis, the use of preimplantation genetic testing, and the number of ETs, Cox regression showed that there were no statistically significant differences between the BMI groups (HR: 0.94 [95% CI: 0.7–1.2]; p = 0.59). When calculating CLBRs considering EmbRs, there was a similarity between the BMI groups (p = 0.57). However, there were no statistically significant differences in the adjusted Cox regression (HR: 0.93 [95% CI: 0.7–1.2]; p = 0.51). Finally, when calculating CLBRs considering OUs, the results were comparable among BMI subgroups (p = 0.75), and there were no statistically significant differences with adjusted Cox regression (HR: 0.95 [95% CI: 0.8–1.2]; p = 0.66). In conclusion, paternal BMI was not associated with clinical reproductive outcomes when considering the ETs, EmbRs, or OUs needed to reach the first liveborn (LB).